제7회 전국동시지방선거 중 기초의원선거에서의 정당 내 기호 순서와 득표 순서의 관계 분석 - 김혁주; Hyuk Joo Kim (Ŭngyong tʻonggye yŏnʼgu, 2018)
2018년 6월 13일에 실시된 제7회 전국동시지방선거 중 기초의원선거에서의 동일 정당 내의 기호 순서와 득표 순서를 분석하여 기호 순서가 득표 순서에 미치는 영향을 살펴보았다. 동일 정당의 후보가 2명인 경우와 3명인 경우, 4명인 경우로 나누어 분석하였는데, 대부분의 경우에 ‘가’ 기호를 배정받은 후보가 동일 정당 내의 타 후보에 비해 많이 득표한 것으로 밝혀져서 대책 마련이 필요한 것으로 나타났다. 또한 더불어민주당의 정당 내 후보가 2명인 경우와 자유한국당의 정당 내 후보가 2명인 경우 관내투표와 관외사전투표 간에 투표 성향의 차이가 있는 것으로 나타났다. We examined the relationship between the order of signs and the order of vote within parties in electing local district councilors during the 7th nationwide local election held on June 13th, 2018. We analyzed election data for respective cases that include two, three, four candidates within the same party. In most cases, the candidate with sign ‘Ga’ gained more than other candidates in the same party, showing a need for provisional measures. In addition, a difference in voting tendency was found between in-house voting and early outside voting when there were two candidates in the Democratic Party of Korea as well as for when there were two candidates in the Liberty Korea Party.